2011
DOI: 10.1007/s10096-011-1470-0
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogens in acute diarrhea: a general practice-based study in a Nordic country

Abstract: The epidemiology of infectious diarrhea influences the microbiological investigation of the disease, and is best elucidated through prospective studies. We undertook such a study in a Nordic country. Patients of all age groups who had acute diarrhea were recruited prospectively from general practice clinics in Iceland. They completed a questionnaire and provided stool samples for the detection of pathogenic viruses, bacteria, and parasites. Of the 464 recruited patients, 211 (45%) had 224 infections. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…11,12 The stool of different trait was also respective of specific bacteria, such as watery stool frequently observed in Salmonella infection and bloody stool in Shigella infection, in agreement with other reports. 17,37 Our analysis reveals that although there are differences between clinical symptoms, there are also many overlaps.…”
Section: Discussionsupporting
confidence: 90%
“…11,12 The stool of different trait was also respective of specific bacteria, such as watery stool frequently observed in Salmonella infection and bloody stool in Shigella infection, in agreement with other reports. 17,37 Our analysis reveals that although there are differences between clinical symptoms, there are also many overlaps.…”
Section: Discussionsupporting
confidence: 90%
“…Enteric bacterial pathogens were isolated using traditional diagnostic techniques from 10z of patients with acute diarrhea, which falls within the previously reported range of 4.8z to 55.1z (6,(8)(9)(10). It should be noted that variations pertaining to geographical area, the types of enteric pathogens, and diagnostic methods were observed in these studies.…”
Section: Discussionsupporting
confidence: 81%
“…Our analysis of the association between patientrelated factors and different pathogen groups (viral, bacterial, or mixed infections) confirms some of the findings of Dutch and Nordic studies [22,23]. Nausea, living in a suburb, and autumn or winter infection correlated positively with viral pathogens, whereas abdominal pain was negatively associated with viral pathogens.…”
Section: Discussionsupporting
confidence: 76%
“…Nausea, place of residence, leukocytosis, and abdominal pain correlated differently with viral and bacterial infections. Many studies have reported that viral pathogens are more likely to be transmitted by person-to-person contact [22][23][24]. Although very few cases were reported to be transmitted by other patients in this study, we found that living in a suburb of Beijing was associated with viral infection.…”
Section: Discussionmentioning
confidence: 36%